7
$\begingroup$

I'm trying to solve for $y$ in terms of $x$ for the expression below.

$$\frac{\ln(x)\ln(y)}{\ln(1-x)\ln(1-y)}=1$$

First I multiplied both sides by $$ \frac{\ln(1-x)}{\ln(x)} $$

to get

$$ \frac{\ln(y)}{\ln(1-y)}=\frac{\ln(1-x)}{\ln(x)} $$

but I don't see how to isolate $y.$ I tried using every technique I know including logarithm properties.

$\endgroup$
2
  • 3
    $\begingroup$ @TheMadcapLaughs: you should delete that at once ! $\endgroup$
    – user65203
    Dec 23, 2019 at 20:01
  • $\begingroup$ Uhm... thats not how logs work... $\endgroup$
    – QC_QAOA
    Dec 23, 2019 at 20:01

2 Answers 2

11
$\begingroup$

The function $f(x)=\dfrac{\ln(1-x)}{\ln(x)}$ is monotonic in its domain $(0,1)$, hence it is invertible. So the relation between $x$ and $y$ is a bijection, and…

$$y=1-x.$$


Interestingly, the function is well approximated by $\left(\dfrac1x-1\right)^{-3/2}$, and a solution with $a$ in the RHS is approximately

$$\left(\dfrac1x-1\right)^{-3/2}=a\left(\dfrac1y-1\right)^{3/2},$$ or

$$y=\frac{1-x}{1+(a^{2/3}-1)x}.$$

$\endgroup$
5
  • 2
    $\begingroup$ +1, very clever $\endgroup$
    – gt6989b
    Dec 23, 2019 at 20:08
  • $\begingroup$ okay I just came to that conclusion myself, thanks $\endgroup$
    – geocalc33
    Dec 23, 2019 at 20:08
  • $\begingroup$ just curious what happens when the $1$ on the RHS becomes $2$ or $3$? $\endgroup$
    – geocalc33
    Dec 23, 2019 at 20:15
  • 1
    $\begingroup$ @Aqua: why should I prove that (which is false) ?? $\endgroup$
    – user65203
    Dec 23, 2019 at 23:05
  • $\begingroup$ Sorry, I meant this. How do you prove $\lim_{x→1−}f(x)=0$? It has nothing to do with the problem, but I'm interested since I want to draw a graph. $\endgroup$
    – nonuser
    Dec 24, 2019 at 7:34
1
$\begingroup$

If it helps: $$\frac{\ln{(y)}}{\ln{(1-y)}} = \frac{\ln{(1-x)}}{\ln{(x)}}$$ $$e^{\frac{\ln{(y)}}{\ln{(1-y)}}} = e^\frac{\ln{(1-x)}}{\ln{(x)}}$$ $$ {{e^{\ln{(y)}}}^{\frac{1}{\ln{(1-y)}}}} = {{e^{\ln{(1-x)}}}^{\frac{1}{\ln{(x)}}}}$$ $$y^{\frac{1}{\ln{(1-y)}}} = (1-x)^{\frac{1}{\ln{(x)}}}$$ $$y^{\ln{(x)}} = (1-x)^{\ln{(1-y)}}$$


From here you can make a substitution: $1-y = t$.


And you get: $$(1-t)^{\ln{x}} = (1-x)^{\ln{(t)}}$$ Since both $\ln{x}$ and $e^x$ are injective it follows: $$x = t$$ And since $t = 1-y$, we conclude: $$y = 1-x $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.